2008
DOI: 10.1519/jsc.0b013e318163441f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intense Military Training on Body Composition

Abstract: Individuals in a structural physical training program can show beneficial changes in body composition, such as body fat reduction and muscle mass increase. This study measured body composition changes by using 3 different techniques-skinfold thickness (SF) measurements, air displacement plethysmography (BOD-POD), and dual-energy x-ray absorptiometry (DXA)-during 9 months of intense training in healthy young men engaged in military training. Twenty-seven young men were recruited from a special faction of the It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
4
17
0
3
Order By: Relevance
“…Other methodologies involve dilution with isotopically labeled water (12), measures of body volume by water displacement (13) or air plethysmography (14), and in vivo neutron activation (15). Nor are the answers always the same in comparisons of these sophisticated technologies (16).…”
Section: The Elusive Clinical Measure Of Adipositymentioning
confidence: 99%
“…Other methodologies involve dilution with isotopically labeled water (12), measures of body volume by water displacement (13) or air plethysmography (14), and in vivo neutron activation (15). Nor are the answers always the same in comparisons of these sophisticated technologies (16).…”
Section: The Elusive Clinical Measure Of Adipositymentioning
confidence: 99%
“…Previous studies have shown that BMI cut-offs for overweight and obesity may not be accurate for particular subpopulations such as Asians (Gallagher et al, 2000;Wang et al, 1994) and individuals with greater lean mass (Malavolti et al, 2008). Among persons with intellectual disability there is documented unique anthropometry (e.g., Lopes, Ferreira, Pereira, da Veiga, & de Marins, 2008;Theodoro, Talebizadeh, & Butler, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have shown that participation in a structured physical training program has a positive impact on health, fitness and performance within tactical populations. Malavolti et al (2008) investigated the effects of rigorous physical training for Navy forces on body composition when performing a 5-day per week physical training program performed for a total of 40 hours per week. After the first phase, BW decreased by 2.2%, which was the result of the loss of fat mass and fat-free mass, and after the second phase, BW increased significantly on account of the fat-free mass.…”
Section: Discussionmentioning
confidence: 99%